PEMBUATAN WEBSITE SEWA KANTOR MENGGUNAKAN REACT JAVASCRIPT - Steven; Viny Christanti Mawardi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2024)
The digitalization process is developed in the communication field. One application of communication is business communication for increasing their transaction like sales, renting, and so on. The reduction COVID-19 pandemic caused companies want to increase the efficiency employees work in office. Many companies rent offices to maximize work efficiency in the office. Renting website is needed to make company easier find the right office as their need. Sewa Kantor website is the website which provides some features like searching the office, monitoring renting transaction by the account, paying the rent and down payment, and reviewing the office after renting. ReactJavascript will be used for developing the design, user interface, and some features on Sewa Kantor Website.